IMPROVING STUDENTS’ ABILITY IN WRITING RECOUNT TEXT THROUGH MULTIMODAL LEARNING MANAGEMENT - Umar Umar (JOURNAL OF LANGUAGE, 2022)
This research is concerned with Improving Students’ Ability in Writing Recount Text through Multimodal Learning Management [MLM]. This research is conducted by adopting qualitative and quantitative designs. Specifically, the researcher adopts experimental research under the quantitative design. The respondents of this research are 64 students at Junior High School of Sumbawa in the Academic Year 2020/2021. The research instrument used in collecting qualitative data is a questionnaire, and in collecting quantitative data is a test. The research results show that 1. Most of the students are more active and enthusiastic during the process of teaching and learning when the media is applied, 2. The students’ writing score test increases after being taught with multimodal learning management and also have good responses toward the learning teaching process, and 3. The students’ mean score of pre-test is 68.72 and post-test is 86.22 in experimental class. Meanwhile, the students’ mean score of pre-test is 63.75 and post-test is 76.03 in control class. There is significant increase of the student’s score in the post-test of experimental compared to the students’ score in the control class. Therefore, it is concluded that MLM can improve students’ writing recount text.